2022
DOI: 10.3390/systems10060203
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Community Detection Approach on Bitcoin Network

Abstract: Community detection is essential in P2P network analysis as it helps identify connectivity structure, undesired centralization, and influential nodes. Existing methods primarily utilize topological data and neglect the rich content data. This paper proposes a technique combining topological and content data to detect communities inside the Bitcoin network using a deep feature representation algorithm and Deep Feedforward Autoencoders. Our results show that the Bitcoin network has a higher clustering coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recently, with the development of deep learning [2][3][4][5][6][7][8], various studies on deeplearning-based distinguishers [9,10] have been presented [11][12][13][14][15][16][17][18][19][20][21]. Deep learning is wellsuited for probabilistically distinguishing data that satisfy differential characteristics, as it has the capability to make probabilistic predictions about data.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the development of deep learning [2][3][4][5][6][7][8], various studies on deeplearning-based distinguishers [9,10] have been presented [11][12][13][14][15][16][17][18][19][20][21]. Deep learning is wellsuited for probabilistically distinguishing data that satisfy differential characteristics, as it has the capability to make probabilistic predictions about data.…”
Section: Introductionmentioning
confidence: 99%
“…The findings demonstrated how well the suggested deep learning with hybrid optimisation works for identifying communities in large networks. Essaid et al [16] presented a method for detecting communities inside the Bitcoin network that uses a deep feature representation algorithm and Deep Feedforward Autoencoders. Their findings demonstrated that, compared to a random P2P network, the Bitcoin network has a stronger clustering coefficient and community structure.…”
Section: Introductionmentioning
confidence: 99%